Factors Affecting Disseminated Intravascular Coagulation (DIC) in Post Partum Women: A Meta Analysis - Musyawamah Musyawamah; Lili Farlikhatun (Global Health Science Group, 2023)
Disseminated intravascular coagulation (DIC) is one of the risk factors that can increase mortality with a prevalence of about 82% when bleeding occurs. Information on how influential maternal characteristics are to the incidence of DIC in postpartum mothers will be very useful in detecting and performing care, however. Indonesian researchers are still lacking in conducting studies on the impact and influence of maternal characteristics with the incidence of DIC on postpartum mothers. The purpose of this meta-analysis was to find out what factors influence the incidence of DIC in postpartum mothers. Primary data is obtained by searching several indexing including: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords